2013
DOI: 10.4025/actascitechnol.v35i1.11132
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation Process (UV/H2O2/ZnO) in the treatment and sterilization of dairy wastewater

Abstract: ABSTRACT. Advanced Oxidation Processes (AOP) have attracted much interest of scientific and industrial communities. Therefore, this process was employed experimentally to determine its efficacy in treating dairy effluents. For this, it was employed an artificial light reactor using photolysis (UV), hydrogen peroxide (H 2 O 2 ) as an oxidant, and zinc oxide (ZnO) as an alternative catalyst. The variables studied in the photocatalysis were: H 2 O 2 , ZnO, under different values of pH, both in relation to the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
10
0
3
Order By: Relevance
“…Also, the decolorization of RB19 being favorable in the acidic environment is due to the electrostatic attractions between the negatively charged functional groups present on the anionic dye and the positively charged MgO NPs surface. A study that investigated the effect of nanoparticles on the treatment of dairy wastewater resulted in an optimum pH of 4 [41]. The contact time is also important in all experimental processes.…”
Section: Response Surface Plotsmentioning
confidence: 99%
“…Also, the decolorization of RB19 being favorable in the acidic environment is due to the electrostatic attractions between the negatively charged functional groups present on the anionic dye and the positively charged MgO NPs surface. A study that investigated the effect of nanoparticles on the treatment of dairy wastewater resulted in an optimum pH of 4 [41]. The contact time is also important in all experimental processes.…”
Section: Response Surface Plotsmentioning
confidence: 99%
“…More commonly, and in a more practical sense though, AOP refers to the treatment processes involving UV light, Ultrasound, Ozone (O 3 ) and hydrogen peroxide (H 2 O 2 ) either singly, serially or in combination with or without catalysts, such as metal ions or semiconductors, [53,56], such as in the equations below . [57]…”
Section: Advanced Oxidation Processes (Aops)mentioning
confidence: 99%
“…Also, H2O2 alone (i.e., without UV power) proved ineffective as for both mineralizing and biodegradability enhancing agent and that the only reactive species was essentially the hydroxyl free radical OH', [20] The effect of operating conditions was observed when measuring via a spectrophotometer at the visible maximum absorption, it was found that the rate of decolorization increased with the initial dosage of H202 up to a maximum and beyond which decoloration was inhibited, [21].…”
Section: Hydrogen Peroxide (H2o2)mentioning
confidence: 99%